Determinants of fresh fish purchasing behavior among Malaysian consumers. - Ahmed, Abdullahi Farah; Mohamed, Zainal Abidin; Ismail, Mohd Mansor (Maxwell Scientific Organization, 2011)
The study investigates demographic and attitudinal characteristics that can affect the purchase decisions of marine fish among Malaysian consumers. A survey was conducted on Kuala Lumpur households using structured questionnaires. Seven hundred respondents were randomly interviewed with regard to their buying behaviour pattern, attitude and perception on fresh marine fish consumption. The data were analyzed using a logit binary model. It was found that the size and income of the households, gender, taste and the nutritional value of fresh fish significantly influenced the purchasing behavior of the respondents. The Malaysian seafood sector may find this study useful to encourage further consumer-based studies for promoting the growth of the domestic fresh marine fish and seafood market in general.